Is chronic postsurgical pain surgery-induced? A study of persistent postoperative pain following breast reconstruction. (February 2018) - Roth, Randy S.; Qi, Ji; Hamill, Jennifer B.; Kim, Hyungjin M.; Ballard, Tiffany N.S.; Pusic, Andrea L.; Wilkins, Edwin G.
Abstract: Background: Chronic postsurgical pain (CPSP) is a reported risk for women undergoing breast reconstruction, but it remains unclear that such persistent pain is induced by reconstructive surgery. To address this concern, this prospective cohort study examined the prevalence of and risk factors associated with CPSP among women undergoing breast reconstruction. Materials and methods: Women (n = 1996) recruited for the Mastectomy Reconstruction Outcomes Consortium (MROC) Study were assessed preoperatively and at two-years postoperatively for relevant medical/.surgical variables, pain experience, body physical well-being, anxiety, depression, and reconstruction procedure type and characteristics. Results: Nearly half of the entire sample reported some level of preoperative pain. At two years there were statistically significant but not clinically meaningful increases in both pain intensity and chest/upper body discomfort but a decrease in affective pain rating. Average clinical pain severity was strikingly similar for preoperative and postoperative assessments. Preoperative levels of pain, acute postoperative pain, and (marginally) level of depression held consistent relationship at two-year follow-up with all outcome measures. Autologous flap reconstruction was associated with more severe CPSP compared to TE/I reconstruction. Older age, higher BMI, bilateral reconstruction, and adjuvant radiation and chemotherapy were associated with CPSP and chest/upper body discomfort for at least one outcome measure at two years. Conclusions: The substantial rate of preoperative pain and comparable prevalence of preoperative and postoperative pain ratings suggest that persistent pain after breast reconstruction may not necessarily reflect surgery-induced pain. Future research will need to determine those factors that contribute to long-term pain following breast reconstruction. Highlights: Nearly half of women undergoing breast reconstruction report pain prior to surgery. There is no meaningful change in pain prevalence following reconstructive surgery. Preoperative and acute postoperative pain predict chronic pain after reconstruction. Greater study design rigor necessary to determine risk of post-reconstruction pain.